Adaptation Strategies, Practices and Challenges of Afghans in Iran and the Role of Digital Interaction - Jauhiainen, Jussi S. (Routledge, 2026)
This article examines the adaptation strategies and challenges of Afghans in Iran, which hosts over three million Afghans across diverse legal, economic, and social contexts. Based on survey data from more than two thousand Afghan respondents—refugees, legally authorised migrants, and undocumented individuals—supplemented by field observations, the study identifies differentiated and constrained adaptation trajectories, with particular attention to the role of Afghans’ digital interaction. Afghan adaptation in Iran is shaped by tensions between individual agency, restrictive institutional frameworks, and societal structures. While some Afghans seek assimilation or integration, barriers imposed by Iranian authorities and host-society resistance largely impede this. Many respond through strategies of spatial separation grounded in strong Afghan identity affiliations and reinforced by digitally mediated ties with Afghanistan and co-nationals. Undocumented unemployed Afghans face the greatest risk of marginalisation, exacerbated by Iran’s economic decline and the pre- to post-pandemic crises. Adaptation is a stratified and dynamic process shaped by legal status, economic precarity, and digital practices.